La mediación como medio alternativo de solución de conflictos y su incidencia en la fijación de pensiones alimenticias de las niñas, niños y adolescentes en el centro de mediación en el consejo de la judicatura del cantón Riobamba durante el periodo enero- agosto 2016. - Garcia Silva, Lissette Julieta (2017)
This is a very important issue since this investigation job tries to make the sytem knows a way that is not attended to and solved with executive character for the parents, the needs of the interested parties to fix a pension in favor of the minors, as long as this Agreement is not unconstitutional or unlawful. Mediation consists in carrying out a voluntary, extrajudicial procedure, in which the parties who are submitted to the conflict, sign an act in which they agree on the monthly value that the father or mother deposits monthly in favor of the minors. Ecuadorian law, through the Constitution (Art. 190) and the Arbitration and Mediation Act (Article 43 et seq.), Establishes mediation as a conflict resolution procedure whereby parties, assisted by a mediator, Who is a neutral person, strive to reach a satisfactory agreement. The right to food allows children and adolescents to meet their basic needs for food, clothing, housing, health, education, etc .; The same that is usually requested by the parent with whom the child is found and who, at times, initiates a legal action to claim payment of that right, or failing that, they resort to alternative methods of conflict resolution. The Mediation Act is the written document stating the obligations of the parties, and has an enforceable judgment and res judicata and can be demanded to be faithfully fulfilled. This investigation job has a lot importance as a legal contribution, for the study and professionalization of the students of the Law School, authorities, teachers, mediators and society in general; For their knowledge and practice according to law applying it with fairness and justice for the good of everybody .